Women’s expectations and experiences of rupture of membranes and views of the potential use of reagent pads for detecting amniotic fluid - Spiby, Helen; Borrelli, Sara E.; Hughes, Anita J. (Wiley, 2017)
AIMS: To explore first time mothers’ expectations and experiences regarding rupture of membranes (RoM) at term, and their views on the potential use of reagent pads that detect amniotic fluid. BACKGROUND: There is little information available on women’s experiences of spontaneous rupture of membranes, or interest in utilising methods to confirm rupture of membranes (e.g. reagent pads). DESIGN: Descriptive qualitative study, utilising focus groups and telephone interviews with women during pregnancy and after the birth of their first baby. Thematic analysis was undertaken to analyse women’s responses. METHODS: Ethics committee approval was obtained. Twenty-five women participated in the study of whom 13 contributed both during pregnancy and postpartum between October 2015 and March 2016. FINDINGS: Three overarching themes emerged from the data from women’s expectations and experiences: uncertainty in how, when and where membranes may rupture; information which was felt to be limited and confirmation of rupture of membranes. The potential use of reagent pads met with varied responses. CONCLUSION: Women were interested in having facts and figures regarding RoM, such as characteristics of liquor; volume and probability of membranes rupturing spontaneously at term. Use of a pad as a means of confirmation was viewed as helpful, although the potential for increasing anxiety was raised.